Digital convergence in Ecuadorian media: Some strengths and weaknesses - Rodriguez Hidalgo, C. (2017)
Convergence in mass media goes beyond the simple integration of the act of production, the usage of multi-media, and remodeling management. It refers to a multi-dimensional process that affects the technological, business, and professional fields, as well as users of mass media, thereby promoting the integration of tools, spaces, work methods, and previously disaggregated languages. Ecuadorian media began to seek convergence in 1998. This article analyzes the state of the art of digital convergence in Ecuador based on two case studies: El Telégrafo and El Universo. The conclusions of this study stress the need for information provider companies to assume the challenges that are implied in reaching audiences that are becoming more and more diverse.